1995
DOI: 10.1111/j.1432-1033.1995.864_3.x
|View full text |Cite
|
Sign up to set email alerts
|

Carotene Desaturation is Linked to a Respiratory Redox Pathway in Narcissus Pseudonarcissus Chromoplast Membranes

Abstract: The enzymic activity of phytoene desaturase in Nurcissus pseudonarcissus chromoplast membranes depends in an essential way on the redox state of its environment. Here, the main redox-active components are quinones and tocopherols. Quinones (oxidized) act as intermediate electron acceptors in the desaturation reaction, as can be shown in reduced, hydroquinone-rich membranes. However. their complete oxidation by ferricyanide treatment of membranes leads to inhibition of the desaturation activity and, under these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 30 publications
1
64
0
Order By: Relevance
“…In its unusual dimeric form it is a member ofthe respiratory redox pathway, involved as a redox mediator in influencing the redox state of membrane-bound quinones. Thus it is also involved in influencing the kinetic behavior of phytoene desaturation (Nievelstein et aL, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In its unusual dimeric form it is a member ofthe respiratory redox pathway, involved as a redox mediator in influencing the redox state of membrane-bound quinones. Thus it is also involved in influencing the kinetic behavior of phytoene desaturation (Nievelstein et aL, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Whether IM also participates in the redox reactions involving these cofactors or whether this part of the whole desaturation process is fulfilled by a separate redox protein is not known. In fact, such a redox protein (a NADPH:quinone oxidoreductase) has been described in nonphotosynthetic plastids (Nievelstein et al, 1995). However, in this study, the latter redox protein is assumed to function differently, namely, in a coreduction-like mechanism that could provide the driving force of the desaturation reaction.…”
mentioning
confidence: 88%
“…The interaction of PDS with the electron transfer chain is unspecific as evidenced by the fact that when expressed in Escherichia coli cells both plant enzymes are able to mechanistically link to the bacterial respiratory redox chains (Mayer et al, 1990;Nievelstein et al, 1995). An analogous situation exists in cyanobacteria where plastoquinol can be oxidized in darkness because the electron transport reactions of photosynthesis and respiration are linked in the same membranes (Sandmann and Malkin, 1984).…”
Section: Involvement Of Orr In the Carotenoid Biosynthetic Pathwaymentioning
confidence: 99%
“…In earlier studies, the involvement of quinones in carotenoid desaturation was demonstrated biochemically (Mayer et al, 1990) and genetically (Norris et al, 1995). It was further discovered that phytoene desaturase activity responded to the redox state of the plastoquinone (PQ) pool (Nievelstein et al, 1995). In chloroplasts, PQ oxidoreduction status can be modulated by linear electron transfer and also by one of the two alternative electron pathways operating around photosystem I (PSI; Bukhov and Carpentier, 2004;Johnson, 2005).…”
Section: Introductionmentioning
confidence: 99%